2010
DOI: 10.3393/jksc.2010.26.5.339
|View full text |Cite
|
Sign up to set email alerts
|

Relation of the Expression of Cyclooxygenase-2 in Colorectal Adenomas and Adenocarcinomas to Angiogenesis and Prognosis

Abstract: PurposeRecent studies have shown that cyclooxygenase (COX)-2 may be involved in tumor growth, invasion and apoptosis in various carcinomas. Vascular endothelial growth factor (VEGF) has a potent angiogenic activity, and COX-2 promotes angiogenesis by modulating angiogenic factors, including VEGF. Endothelial growth factor receptor (EGFR) is considered as a factor of cell growth, maturation and cell death. The current study was designed to investigate the possible roles of COX-2 in colorectal tumor progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Wasilewicz et al showed that the expression of COX-2 in colon polyps is associated with polyp length (20). In addition, Han et al found higher COX-2 expression in patients with colorectal cancer who also had polyps, but consistent with our results, there was no correlation between the clinicopathological variables and COX-2 levels (21). Here we measured, for the first time, plasma COX-2 protein levels in control, polyp, and cancer groups; however, no significant differences were found.…”
Section: Discussionsupporting
confidence: 84%
“…Wasilewicz et al showed that the expression of COX-2 in colon polyps is associated with polyp length (20). In addition, Han et al found higher COX-2 expression in patients with colorectal cancer who also had polyps, but consistent with our results, there was no correlation between the clinicopathological variables and COX-2 levels (21). Here we measured, for the first time, plasma COX-2 protein levels in control, polyp, and cancer groups; however, no significant differences were found.…”
Section: Discussionsupporting
confidence: 84%
“…Among them, TNFα or IL-1β induce the expression of growth factors, stimulate epithelial tumor motility and tumor angiogenesis ( 30 , 31 ). Another proinflammatory molecule commonly upregulated in colon cancer, COX-2, has been implicated in the growth and progression of colorectal cancer via multiple pathways ( 32 – 34 ) including the acquisition of resistance to apoptosis and promoting angiogenesis through VEGF production ( 35 , 36 ). Moreover, a decrease in COX-2 expression at RNA levels in total liver caused by OOS administration might be related to a reduction in VEGF levels ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Han et al ( 30 ) correlated the expression of COX-2 with the tumor size in 50 colorectal adenomas and 40 carcinomas and did not determine a significant relationship. In the present study, the association between the expression of COX-2 and the degree of dysplasia, size, and histological type of the adenomas was not significant.…”
Section: Discussionmentioning
confidence: 99%